2017
DOI: 10.1007/s10787-017-0330-7
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide induced stomach and duodenal lesions as a NO-system disturbance in rats: l-NAME, l-arginine, stable gastric pentadecapeptide BPC 157

Abstract: We revealed a new point with cyclophosphamide (150 mg/kg/day intraperitoneally for 7 days): we counteracted both rat stomach and duodenal ulcers and increased NO- and MDA-levels in these tissues. As a NO-system effect, BPC 157 therapy (10 µg/kg, 10 ng/kg, intraperitoneally once a day or in drinking water, till the sacrifice) attenuated the increased NO- and MDA-levels and nullified, in rats, severe cyclophosphamide-ulcers and even stronger stomach and duodenal lesions after cyclophosphamide + L-NAME (5 mg/kg i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 50 publications
2
57
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] BPC 157 also acts as a free radical scavenger, counteracts free radical-induced lesions, and normalizes NO and MDA levels in tissues and during ischemia and reperfusion. 101,113,114,[116][117][118] Subsequent studies from other groups 2,96-101 have confirmed our original findings. [65][66][67][68][69][70][71][72][73][74][75][76][77][78] Pleotropic effects involving distinctive receptors, including VEGFR2 and growth hormone receptors, distinctive pathways, including VEGFR2-AKT-eNOS, ERK ½, FAK-paxillin, FoxO3a, p-AKT, p-mTOR and p-GSK-3β, and distinctive loops, including stimulation of the egr-1 gene and its corepressor gene naB2, and counteraction of increases in pro-inflammatory and procachectic cytokines, 2,[96][97][98][99][100][101] likely minimize the inherent lack of full understanding of the mechanisms that may be involved.…”
Section: Homeostasissupporting
confidence: 81%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] BPC 157 also acts as a free radical scavenger, counteracts free radical-induced lesions, and normalizes NO and MDA levels in tissues and during ischemia and reperfusion. 101,113,114,[116][117][118] Subsequent studies from other groups 2,96-101 have confirmed our original findings. [65][66][67][68][69][70][71][72][73][74][75][76][77][78] Pleotropic effects involving distinctive receptors, including VEGFR2 and growth hormone receptors, distinctive pathways, including VEGFR2-AKT-eNOS, ERK ½, FAK-paxillin, FoxO3a, p-AKT, p-mTOR and p-GSK-3β, and distinctive loops, including stimulation of the egr-1 gene and its corepressor gene naB2, and counteraction of increases in pro-inflammatory and procachectic cytokines, 2,[96][97][98][99][100][101] likely minimize the inherent lack of full understanding of the mechanisms that may be involved.…”
Section: Homeostasissupporting
confidence: 81%
“…112 Finally, the BPC 157-NOsystem-relation includes complex healing failure, proved by the fistulas healing, 82,[84][85][86] or particular anastomoses healing 88 or vessel occlusion 101,113 or cytostatic agents application (i.e., doxorubicin, cyclophosphamide). 41,114 The notation that BPC 157-NOsystem-relation interferes with the effects of neuroleptics merits further elaboration. 115,116 Finally, BPC 157 application lead to normalization of NO-level in tissues as well as counteraction of free-radicals formation.…”
Section: Bpc 157 Stomach Cytoprotection Concept → Wound Heal-mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the antioxidant system may play an essential role during midgut invasion, which is however, largely disabled in invaded honeybees (Dussaubat et al., ). Thus, although this was not specifically investigated in insect midgut, it should be noted that various free radicals‐induced lesions in other organs were also counteracted by BPC 157 administration (Ilic et al., ; Luetic et al., ; Sikiric, Seiwerth, et al., ), and in particular, ischemia/reperfusion injuries in rat colitis (Duzel et al., ). Thus, it was suggested that BPC 157 may serve as a possible antioxidant (i.e., BPC 157 contains four carboxylic groups, all of them could be active in scavenger process and if reactivated [e.g., by glutathione or by enzymes], the overall beneficial activity could be very high; Duzel et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, this effect may be the cause or a consequence of the beneficial effects of BPC 157 on related disturbances [1][2][3][4][5][6][7][8][9][10][11]. As demonstrated, BPC 157 counteracts free radical formation and free radical-induced lesions [32,[82][83][84]. An interesting point would be the use of the same dose range in BPC 157 studies [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 93%